Demonstration of a geostatistical approach to physically consistent downscaling of climate modeling simulations. Issue 1 (24th January 2013) - Jha, Sanjeev Kumar; Mariethoz, Gregoire; Evans, Jason P.; McCabe, Matthew F.
Key Points Downscaling of climate model data by the Direct Sampling method was demonstrated Downscaled temperature, soil moisture and latent heat show excellent results Error analysis of the downscaled variables and their correlations are presented